Pemberdayaan Generasi Muda Desa Melalui Podcast Kearifan Lokal: Revitalisasi Nilai Gotong Royong di Era Media Sosial - Hamka, Hamka; Asrul, Asrul; Liputo, Burhan (-, 2025)
Social changes resulting from the development of digital technology have led to a shift in traditional social values among the younger generation, particularly the value of gotong royong (mutual cooperation), which is a distinctive characteristic of Indonesian society. This study aims to empower rural youth through podcast media as a means of revitalizing local wisdom values in the era of social media. The method used is a participatory approach involving training, mentoring, and the production of digital content based on local wisdom. The results of the community engagement program show that podcasts can be an effective medium for disseminating the value of gotong royong, enhancing digital literacy, and revitalizing social awareness among the younger generation.